Comparing reproductive health communication with mothers between urban and rural adolescent girls - Tamanna, Tanjeemay; Priyanka, A. S.; Sourav, D. G.; Moni, Mahfuja Khatun; Zaman, Rakib Uz; Jahan, Nusrat; Tasmia, Khandokar; Nazmul Husain, M. (International Journal of Research in Medical Sciences, 2024)
Background: Reproductive health (RH) communication between mothers and adolescent girls is critical for fostering knowledge and healthy behaviors. This communication varies significantly between urban and rural settings due to different socio-cultural contexts and access to information. The aim of this study was to compare RH communication with mothers between urban and rural adolescent girls. Methods: This cross-sectional comparative study was conducted from January to December 2020 in Mithapukur upazila (rural) and Rangpur city (urban) in Bangladesh. A total of 112 adolescent girls aged 14 to 17 from class 9 and 10 were interviewed, with 56 girls from each area. Results: Socio-demographic characteristics were similar in both groups. In both urban and rural areas, 67.9% of respondents communicated with their mothers about RH, while 32.1% did not. In the past six months, 58.9% of urban and 57.1% of rural girls had no RH discussions. Menstruation and pubertal changes were the most common topics in both areas, while other RH topics were less frequently discussed. Discussions often began at the onset of menstruation or between ages 9-12, with some starting during high school entry or initiated by the girls themselves, though 32.1% in both areas had not started discussions. The majority were only informed about necessary RH parts. Conclusions: The results of this study demonstrate that RH communication among urban adolescent girls was higher as compared to the rural adolescent girls.